Improving the milling machine competency learning outcomes through industrial project-based learning for vocational school students - Heri Yudiono; Wirawan Sumbodo; Salim Salim; Rizki Setiadi (Jurnal Pendidikan Vokasi, 2019)
This research is motivated by the implementation of conventional learning. Besides, student learning motivation is still low due to student activities that are less centered on making workpieces that are suitable for work in the industry. Learning outcomes show that only 55.88% of students reach Minimum Completeness Criteria (Kriteria Ketuntasan minimum or KKM). The design and learning of productive machining competencies that are in accordance with the needs of the industry influence students' experience and learning outcomes. This study aims to analyze the results of industrial project-based learning (InPro-BL) milling machine competency learning outcomes in SMK Negeri 1 Semarang. The method used in this study is Class Action Research (CAR) through four stages: (1) planning, (2) implementation of actions, (3) observation and evaluation, (4) reflection. The samples were 34 students of class XII of Mechanical Engineering. The data were collected using product assessment instruments to measure dimensional accuracy, timeliness, level of disability, level of smoothness, and work attitude. This study was descriptive quantitative, and qualitative. The results of the study show that InPro-BL is effective in improving the learning outcomes of milling machine competencies. In Cycle I,  there is an increase in learning outcomes, from 19 students who completed the KKM to 25 students or 73.52%. In Cycle II, there are 88.23% of students passed the KKM. These results can be improved by paying attention to the management of learning time through the block system, teacher's understanding of industrial-project-based learning, and industry guest teachers mentoring every learning process.